Abnormal hemoglobin A1C (hba1c) value in a men patient with diabetic pedis ulcer and uncontrolled reactive - Michael Wiyandi Sudjalmo; Hernando Sulianto; Winarno W (Institute of Computer Science (IOCS), 2023)
Glycated hemoglobin (HbA1c) is the gold standard test to identify average plasma glucose in the last 2-3 months with a fast, convenient and accurate test since 1968 for DM diagnostic. Indonesian Society of Endocrinology (PERKENI) 2021 determines that the diagnosis of HbA1c is above 6.5%. HbA1c assays can be used in diagnosis and treatment to identify clinical scenarios and factors contributing to bias. It is important to recognize the factors that can cause results to be inaccurate. The following is a case presentation of abnormal HbA1c values in a man patient with diabetic foot ulcers and uncontrolled reactive hyperglycemia who was treated at a hospital in Semarang.